Adaptation to high altitude: Effects of small changes in the regulatory behavior of the andean chicken hemoglobin - Kister, Jean; Caron, Genevieve; León-Velarde, Fabiola; Pagnier, Josée; Poyart, Claude (Acta Andina, 2025)
A strain of high altitude chickens (Gallus gallus) displaying a high oxygen affinity hemoglobin has been discovered in the Peruvian Andes. We addressed the question of the molecular mechanism possibly at the origin of the high altitude adaptation of these chickens. The role of small changes of the intracellular concentration of inositol pentaphosphate (IPP), the main allosteric effector of hemoglobin in avian erythrocytes, has been postulated. We have studied the blood from andean and sea-level born chickens. The oxygen affinities of fresh red blood cells (RBC) suspensions are significantly increased in andean compared to sea-level chicken blood. The values of the Hill coefficients at half-saturation (n50) are higher for chicken RBC than those observed for mammalian RBC. This may suggest the existence of a molecular aggregation process inside the deoxygenated, highly concentrated cells of both avian types. For the stripped purified hemolysate solutions of the two types of chickens, the oxygen affinities are identical in phosphate-free buffer. indicating that the intrinsic oxygen affinities of andean and sea-level Hbs are the same. Upon addition of inositol hexaphosphate (IHP), a strong allosteric effector of avian hemoglobins, we observed a small but significant increase (about 20%) of the oxygen affinity of the andean relatively to sea-level hemolysates. Our results also suggest that the difference in affinity between the sea-level and andean blood may be due to an adaptative process possibly related to a slight decrease in the concentration and/or of the activity of the main cellular effector IPP, rather than to a structural abnormality of the hemoglobin.